Demonstration of borna disease virus RNA in peripheral blood mononuclear cells derived from domestic cats in Japan. - Nakamura, Y (1996)
Borna disease virus (BDV) naturally infects horses, sheep, and several other species, including humans, and it is believed to be related to neurological disorders. BDV infection in domestic cats has also been demonstrated by serological assays. We demonstrated for the first time BDV RNA in peripheral blood mononuclear cells from 11 of 83 (13.3%) randomly selected domestic cats in Japan by nested reverse transcriptase-PCR. The BDVs from cats were similar to but slightly different from those from horses and humans, as shown by sequencing the reverse transcriptase-PCR products. None of the cats was positive for both BDV RNA and anti-BDV antibodies.